Tvorba českého znalostního dotazníku pro pacienty s diabetem mellitem: vyhodnocení obtížnosti položek a jeho vnitřní konzistence - Šoukalová, Kristýna; Prázný, Martin; Doležalová, Barbora; Holubová, Marie (Ošetrovateľstvo, 2020)
Aim: To describe the process of two final phases of creating a knowledge questionnaire for patients with type 1 diabetes mellitus (DM1T) and type 2 diabetes mellitus (DM2T), which consisted in evaluating the difficulty of its items and its internal consistency. Methods: The last phase of data collection for calculating the difficulty of items and the internal consistency of the questionnaire took place in the period 08–11/2018. From the results obtained from 258 patients (DM2T 226; DM1T 32), the difficulty of the questionnaire items was evaluated by calculating the value of difficulty Q (value 0 = simple item; value 1 = difficult item). The reliability of the created tool was evaluated by calculating the coefficient of internal consistency according to the formula Kuder-Richardson 20 (minimum acceptable value 0.7). Results: The difficulty values of the items ranged from 0.24–0.72. According to generally accepted recommendations, none of the items falls into the area of extremely simple or extremely difficult items. The internal consistency for the individual parts of the questionnaire ranged from 0.70–0.88. Conclusion: The items of the newly created knowledge questionnaire can be evaluated as average difficult based on the calculation of the difficulty from the data obtained from the respondents. All parts of the questionnaire reached a minimum acceptable value of internal consistency. The created questionnaire is verified and suitable for use in Czech-speaking patients.
Keywords: diabetes mellitus; lidé; komplikace diabetu; vzdělávání pacientů jako téma; průzkumy a dotazníky; Nursing Care; Humans; Surveys and Questionnaires; Patient Education as Topic; Diabetes Mellitus; Diabetes Complications; ošetřovatelská péče